Nonpoint Source Pollution. (1st October 2017) - Ahmad, Zaki Uddin; Sanin, Maxim; Lian, Qiyu; Zappi, Mark; Gang, Daniel Dianchen
Abstract : This research article depicts a comprehensive review of scientific research advancement on nonpoint source pollution (NPS) in 2016. The causes, impacts, and methods used to mitigate nonpoint source pollution were reviewed. In addition, the assessment of nonpoint source pollution using different modeling techniques, coupled with evaluation and management tools were reviewed. Innovative technologies to reduce nonpoint source pollution were also reviewed in this paper.